Growth and metabolic responses of orange spotted grouper Epinephelus coioides (Hamilton, 1822) fingerlings at different salinity regimes - Xavier, Biji; Megarajan, Sekar; Ranjan, Ritesh; Dash, Biswajit; Sadhu, Narasimhulu; Siva, Ponnaganti; Ghosh, Shubhadeep (Indian Journal of Fisheries, 2021)
A feeding trial was conducted for 60 days to delineate the effect of different salinities on growth and metabolic responses in fingerlings of orange spotted grouper Epinephelus coioides (Hamilton, 1822). The grouper fingerlings (N=1050; Av. wt. 2.0±0.01 g) were distributed equally into seven treatments of varying salinities viz., 5±1‰ (T1), 10±1‰ (T2), 15±1‰ (T3), 20±1‰ (T4), 25±1‰ (T5), 30±1‰ (T6) and 35±1‰ (T7) in triplicates. Fingerlings were fed with commercial diet containing 45% crude protein and 10% lipid. Results from the experiment concluded that growth performance of fingerlings of T4 group was better with minimum metabolic enzyme activity. The liver glycogen was significantly lower (p